Intuitive Dualism and Afterlife Beliefs: A Cross‐Cultural Study. Issue 6 (25th June 2021) - Barrett, H. Clark; Bolyanatz, Alexander; Broesch, Tanya; Cohen, Emma; Froerer, Peggy; Kanovsky, Martin; Schug, Mariah G.; Laurence, Stephen
Abstract: It is widely held that intuitive dualism —an implicit default mode of thought that takes minds to be separable from bodies and capable of independent existence—is a human universal. Among the findings taken to support universal intuitive dualism is a pattern of evidence in which "psychological" traits (knowledge, desires) are judged more likely to continue after death than bodily or "biological" traits (perceptual, physiological, and bodily states). Here, we present cross‐cultural evidence from six study populations, including non‐Western societies with diverse belief systems, that shows that while this pattern exists, the overall pattern of responses nonetheless does not support intuitive dualism in afterlife beliefs. Most responses of most participants across all cultures tested were not dualist. While our sample is in no way intended to capture the full range of human societies and afterlife beliefs, it captures a far broader range of cultures than in any prior study, and thus puts the case for afterlife beliefs as evidence for universal intuitive dualism to a strong test. Based on these findings, we suggest that while dualist thinking is a possible mode of thought enabled by evolved human psychology, such thinking does not constitute a default mode of thought. Rather, our data support what we will call intuitive materialism —the view that the underlying intuitive systems for reasoning about minds and death produce as a default judgment that mental states cease to exist with bodily death.